ANALISIS KINERJA PERUSAHAAN DENGAN KONSEP BALANCED SCORECARD PADA SEKTOR PERBANKAN (Studi Kasus Pada BNI Sukoharjo) - Suhesti Ningsih (JURNAL ILMIAH EDUNOMIKA, 2021)
This research was conducted with the aim of knowing the partial and simultaneous influence of financial perspective, customer perspective, internal business process perspective, and learning and growth perspective on the performance of Bank Negara Indonesia (BNI). The research was conducted using a quantitative descriptive approach, with a sample of 33 respondents. Technical analysis of the data using multiple linear regression analysis, ui F, t test and R2 test. The results of the research from the results of the F test and t test which were carried out on the financial perspective had a partial effect on the performance of Bank Negara Indonesia BNI. The customer perspective affected the performance of Bank Negara Indonesia (BNI). simultaneously on the performance of Bank Negara Indonesia (BNI). The results simultaneously obtained a calculated F value of 28.615 > F table 2.714 with a probability of 0.000 (p value